Molecular Docking of Quinoline-1,2,3-Triazole Derivatives as Potential Anti-Breast Cancer Agents Targeting Estrogen Receptor-α - Putri, Aisyah; Azra, Fajriah (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2026)
Breast cancer remains one of the leading causes of cancer-related morbidity and mortality among women worldwide. Estrogen Receptor Alpha (ER-α) is a key regulator of ER-positive breast cancer cell proliferation and represents an important target for anticancer drug development. This study evaluated the potential of quinoline-1,2,3-triazole derivatives as ER-α inhibitors using an in silico approach. Fifteen compounds were analyzed through molecular docking against ER-α (PDB ID: 3ERT) using MOE software. Docking validation confirmed the reliability of the protocol with an acceptable RMSD value. All compounds exhibited favorable binding within the active site of ER-α. Among them, compound 5h showed the strongest binding affinity with a docking score of −12.76 kcal/mol, surpassing that of the native ligand.  Interaction analysis revealed the involvement of important amino acid residues, including Glu353, Arg394, Leu387, and Met421. ADMET prediction indicated favorable pharmacokinetic properties. These findings suggest that quinoline-1,2,3-triazole derivatives have potential as anti-breast cancer agents targeting ER-α.